Effect of the residual levofloxacin on hydroponic vegetables with sewage treatment plant tailwater: Microbial community, discharge risk and control strategy - Chen, Huihua; Dai, Duiwu; Yu, Xiangfen; Ying, Liya; Wu, Shengyu; Chen, Ruihuan; Xu, Bentuo; Zhao, Min; Zheng, Xiangyong (Ecotoxicology and environmental safety, 2024)
Tailwater-based hydroponic vegetable is a promising strategy for domestic wastewater recycling. However, the effect of residual antibiotics on the hydroponic vegetable system and the relation between hydroponic culture parameters and the residual water quality are still unclear. Here, the typical antibiotic Levofloxacin (LVFX) was employed, and the effect of LVFX (5 mg/L) on the residual water quality, plant growth and microbial community of water spinach hydroponic culture system were investigated under different hydraulic residence times (HRT). Obvious toxic effects on water spinach were observed, and the highest removal rate of LVFX (about 6 %) and TN (25.67±1.43 %) was observed when HRT was 7 days. Hydroponic culture increased the microbial abundance, diversity, and microbial community stability. To optimize the hydroponic culture, actual sewage plant tailwater spiked with 20 μg/L LVFX, along with three common planting substrates (sponge, ceramsite, and activated carbon) were used for the hydroponic culture of lettuce (seasonal reasons). The inhibition effect of LVFX on the removal of NO3--N and TN was observed even as the LVFX concentration decreased significantly (from 14.62 ± 0.44 μg/L to 0.65 ± 0.07 μg/L). The best growth situation of lettuce and removal rates of NH4+-N, NO3--N, TN, especially LVFX (up to 95.65 ± 0.54 %) were observed in the activated carbon treated group. The overall results indicate the negative effect of residual antibiotics on the hydroponic vegetable systems, and adding activated carbon as substrate is an effective strategy for supporting plant growth and controlling discharged risk. [Display omitted] •Toxic effects of Levofloxacin on water spinach growth were observed in tailwater-based hydroponic culture system.•Hydroponic culture increased the microbial abundance, diversity and microbial community stability.•Levofloxacin affects the removal rates of NH4+-N, NO3--N, TN, TP even at a low concentration of 20 μg/L.•Using activated carbon as planting substrate is favorable for supporting plant growth and controlling discharged risk.